Managing Injuries and Utilizing Protein: A Literature Review on Strategies for Enhancing Athletic Performance in Modern Sports Health - Rahmatil Husni; Muhamad Sazeli Rifki; Arsil Arsil; Yovhandra Ockta (Postgraduate, University of Mataram, 2024)
This study aims to assess the impact of protein utilization and injury management on enhancing athletic performance and recovery in modern sports. Utilizing a qualitative descriptive research model, the study involves a comprehensive review of literature from reputable scientific databases such as Scopus, ScienceDirect, and Google Scholar. Keywords such as